2010
DOI: 10.1371/journal.pgen.1001149
|View full text |Cite
|
Sign up to set email alerts
|

Tight Regulation of the intS Gene of the KplE1 Prophage: A New Paradigm for Integrase Gene Regulation

Abstract: Temperate phages have the ability to maintain their genome in their host, a process called lysogeny. For most, passive replication of the phage genome relies on integration into the host's chromosome and becoming a prophage. Prophages remain silent in the absence of stress and replicate passively within their host genome. However, when stressful conditions occur, a prophage excises itself and resumes the viral cycle. Integration and excision of phage genomes are mediated by regulated site-specific recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
0
22
0
2
Order By: Relevance
“…Yet while the recombination functions of MGIs and KplE1 seem to be organized alike, they are functionally unrelated. In KplE1, the intS gene is tightly regulated by its own product as well as by the TorI protein (34). In contrast, we showed that in MGIs, rdfM is not a transcriptional regulator of int MGI .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Yet while the recombination functions of MGIs and KplE1 seem to be organized alike, they are functionally unrelated. In KplE1, the intS gene is tightly regulated by its own product as well as by the TorI protein (34). In contrast, we showed that in MGIs, rdfM is not a transcriptional regulator of int MGI .…”
Section: Discussionmentioning
confidence: 54%
“…The integrase gene intV2 (VC1758) and the RDF gene vefA (VC1809) of the Vibrio pathogenicity island 2 (VPI-2) are organized in a similar manner (2). This organization also resembles that of the KplE1 prophage, in which the attL site overlaps with the promoter of the intS gene, and the gene coding for the RDF TorI is remotely located, near the attR site (34). Yet while the recombination functions of MGIs and KplE1 seem to be organized alike, they are functionally unrelated.…”
Section: Discussionmentioning
confidence: 77%
“…The integrase gene of KplE1 is transcribed independently from the RDF gene and is always expressed at a sufficient level to support prophage excision in the presence of the cognate RDF (24). However, under noninduced conditions, expression of the torI gene is not sufficient to allow for KplE1 excision.…”
Section: Resultsmentioning
confidence: 99%
“…These prophages integrate into the same argW locus, share a similar genetic organization of the recombination module, and their respective integrase genes are always expressed at low but sufficient levels to promote prophage excision as long as the RDF genes are expressed. A bioinformatics search allowed us to generalize this genetic organization to many prophages in bacterial genomes (24). This analysis, recently updated to more than 2,000 prokaryotic genomes, shows that 57% of the integrase genes associated with tRNA are self-regulated.…”
Section: Bcm Inhibition Of Rho Induces Prophage Hk620 In An Sos-indepmentioning
confidence: 99%
See 1 more Smart Citation